METHODS OF DETERMINING THE SIZE OF NATURAL RESOURCE RENTS AND DIRECTIONS OF IMPROVEMENT - S. Chernyavskiy; N. Zolotarev (Вестник университета)
The article discusses the methodology for determining the size of the natural (mountain) rents, developed and proposed for use in the Russian economy. Analyzes the shortcomings of techniques that are based on «extremely profitable concept of» natural rent (these techniques are based on a comparison of economic indicators, rather than the specific nature of production conditions, and may not be used in economic calculations). When determining the amount of mining rent its calculations should be based on the specific environmental conditions of mining, or indicators reflecting their (standard costs applied production technology).